Coherent strain evolution at the initial growth stage of AlN on SiC(0001) proved by in situ synchrotron X-ray diffraction. (8th April 2020) - Suzuki, Hidetoshi; Ishikawa, Fumitaro; Sasaki, Takuo; Takahasi, Masamitu
Abstract: We carry out real-time in situ synchrotron X-ray diffraction on the growth of GaN and AlN on SiC(0001) substrate by molecular beam epitaxy. At the initial growth stage of GaN/SiC or AlN/SiC heterostructure, the epitaxial overlayer develops affected by defects with the strain interaction between SiC, eventually showing characteristic lattice deformations. GaN was almost relaxed at the initial stage, showing the transition of the growth mode from 3D to 2D at around 4 nm. In contrast, AlN coherently grow on SiC(0001) at the initial stage for 13 nm concomitantly showing lattice deformation with the beneath SiC, subsequently showing gradual lattice relaxation.